Tédio e modernidade em Baudelaire - Castro, Mariana dos Reis Gomes de (2014)
The aim of this work is to circumscribe tedium notion in modernity. The first chapter is dedicated to A Philosophy of Boredom (1999), Lars Svendsen book, which will enable us to differentiate diverse kinds of apathies which occurred along mankind history, by philosophy and literature. The second chapter is destined to verse about some writings which the philosopher Walter Benjamin destined to Charles Baudelaire, notedly the essay On Some Motives in Baudelaire (1939) and some fragments of his survey Paris of the Second Empire (1938). In the third chapter, we will dedicate to the part of the Essays in contemporary psychology (1883), Paul Bourget book, destined to analyse Charles Baudelaire and to insert him in what the literary critic calls nihilism, pessimism. In the fourth chapter we will examine tedium in Baudelaire from the perspective by an Erich Auerbach article and, also, the Jean Starobinski reflections concerning the figure of the melancholic. Finally, we will use passages of Claudio Willer doctorate thesis to think about the body and the death in Baudelaire poems